Effect of post-harvest treatments and storage conditions on bioactive compounds content, moisture content and color stability of orthosiphon stamineus dried leaves - Norawanis Abdul Razak (School of Bioprocess Engineering, 2017)
This research focuses on the key factors of quality evaluation of 0.stamineus dried leaves during storage. Several important storage conditions were manipulated to monitor the physical and chemical changes in 0.stamineus dried leaves, including 0.staminieus extracts. These factors include temperature and relative humidity